Opportunity and Challenges in UX Design for E-Commerce Website - Suadamara, Rein (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
The study of this research focuses on a review approach based on the information collected on the opportunities and challenges in user experience (UX) design for e-commerce websites. The foundation of the study is based on the global expansion of e-commerce which demonstrated the people’s acceptance of e-commerce. Recognizing where there is room for improvements in the UX design is therefore critical. Overcoming the challenges is also important to create the best UX design that answers the user’s need for an e-commerce website. Understanding what users need through the user experience may determine the success of the companies’ e-commerce website, as UX and e-commerce reviews have a very strong correlation. Understanding the main reason that brings customers to make their purchases in an online market is important.  Experiencing a good user experience may lead to customer satisfaction and loyalty, which motivates them to return and make more purchases, as well as to recommend the website to other customers. Companies should make sufficient investments in UX noting that a successful e-commerce website highly depends on a positive UX. Examining earlier well-known research studies of UX design for e-commerce websites is the aim of this study, which will serve as a basis for further extensive research into this topic. Using the review approach, the study determined and evaluated the opportunities and challenges of UX design to improve user satisfaction to increase sales on e-commerce websites. Improving the user experience and user satisfaction will lead the customer to be more motivated in making orders and purchases. Having awareness on the website’s aspects that could have a negative impact to customers may improve the companies’ business process. Hence, research to improve the e-commerce website is key to providing users with a better online purchasing experience. The practical implication of this research is expected to serve as a guide for the development of e-commerce strategies. The findings are expected to enhance the efficacy of the e-commerce website as well as user satisfaction.